2015
DOI: 10.15835/nbha4319746
|View full text |Cite
|
Sign up to set email alerts
|

New Values of Teucrium species: in Vitro Study of Cytotoxic Activities of Secondary Metabolites

Abstract: The cytotoxicity of seven Teucrium species, a long time ago used as a food spices, for beverages and teas preparing, as well as therapeutics for digestive and respiratory diseases, were examined against human cervix adenocarcinoma HeLa, human melanoma Fem-x, human chronic myelogenous leukemia K562 and human breast adenocarcinoma MDA-MB-361 cells. MTT assay was used for determination of target cell survival. The most prominent cytotoxic effect was observed against K562 cells, especially by T. scordioides, T. mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Stankovic et al have demonstrated that the IC50 values of the TP after 72 hours of cells incubation were between 100µg/ml and 200µg/ml that were in correlation with the results of our research. Particularly, the concentration of the TP required to reduce the viability of HeLa cervical adenocarcinoma cells to 50% after 72 hours was 148.02±4.99 µg/ml, for Fem-x human melanoma cells was 199.79±0.30 µg/ml, and for K562 cells chronic myelogenous leukemia's cells, the concentration was 116.75±24.40 µg/ml [20].…”
Section: Discussionmentioning
confidence: 96%
“…Stankovic et al have demonstrated that the IC50 values of the TP after 72 hours of cells incubation were between 100µg/ml and 200µg/ml that were in correlation with the results of our research. Particularly, the concentration of the TP required to reduce the viability of HeLa cervical adenocarcinoma cells to 50% after 72 hours was 148.02±4.99 µg/ml, for Fem-x human melanoma cells was 199.79±0.30 µg/ml, and for K562 cells chronic myelogenous leukemia's cells, the concentration was 116.75±24.40 µg/ml [20].…”
Section: Discussionmentioning
confidence: 96%
“…These compounds in T. polium extract are able to influence a variety of cell functions by inhibiting cell proliferation and migration. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The anticancer properties of T. polium have been shown in some studies on a huge number of cancer cell lines, such as MCF-7 and MDA-MB-231 breast adenocarsinoma, 11 , 12 bladder carcinoma, epidermoid carcinoma (A431), Skmel-3 Melanoma cell line, Saos-2 osteoblastoma, SW480 colon carcinoma, 18 K562 chronic myelogenous leukemia, 19 REYF-1 glioblastoma multiforme, 20 BT20 human breast ductal carcinoma, PC12 mouse pheochromocytoma and A549 human lung adenocarsinoma cell lines. 21 In addition to the antitumor properties of the crude extract of T. polium , different fractions of T. polium have also shown promising antitumor activity , namely, the petroleum ether fraction as the most potent fraction that was examined on U87 cells.…”
Section: Introductionmentioning
confidence: 99%
“…The antiproliferative activity of T. chamaedrys has been examined on several cancer cells with positive results (ABU-DAHAB and AFIFI, 2007;STANKOVIĆ et al, 2015). Previously reported results about cytotoxic activity of methanol extract from T. chamaedrys against HCT-116 cells (STANKOVIĆ et al, 2011) showed remarkable cytotoxic activity, according to fact that crude extracts with IC 50 values ≤ 30 μg/ml are considered as a pharmaceutically active (SUFFNES and PEZUTO, 1990).…”
Section: Effects On Gene Expression Of Biotransformation Enzymes and mentioning
confidence: 99%
“…Previous reports have demonstrated that the T. chamaedrys possessed several biological activities such as antioxidant, antimicrobial, antifungal, etc (STANKOVIĆ et al, 2010). Recently, it has also been reported that T. chamaedrys induces cytotoxic activity against several cell lines, including HCT-116 colorectal carcinoma cells (STANKOVIĆ et al, 2011;STANKOVIĆ et al, 2015). These reports are without data about mechanism of its cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%